A Qualitative meta-analysis of the socioeconomic impacts of offshore wind farms - Mariel Alem; Timo Herberz; Vishnu Sankar Karanayil; Ahmed Ashfaque Hamid Fardin (Center for Science and Technology, IAIN Surakarta, 2020)
Climate change and an increased interest in renewable energy have resulted in a burgeoning wind energy sector. However, in the recent past, wind farms have faced resistance in acquiring permits due to concerns about their long-term effects on the local community. To understand the extent of these externalities, this study qualitatively meta-analyses four socio-economic impacts of interest, namely: house prices, tourism, catalytic effects of supply chain clustering, and social change. Geographically, the analysed reports include Europe, Canada and the US, and deductions are made for the EU. In order to bridge the gap of unavailability of primary data on the wind sector, relevant conclusions are drawn from other comparable sectors. Based on a rigorous review of primary qualitative research, this study concludes that offshore wind farms should be located more than 40 km away from the coast to eliminate risks of housing price devaluation and tourist activity reduction, which would directly affect the economic value of the region. In addition, the study found limited evidence to acknowledge the employment benefits in the local economy and social change in the community due to offshore wind farms. Monitoring mechanisms should be set up to prove or disprove the creation of local employment, crime and substance abuse. Furthermore, the study finds that adequate planning and management can ensure better socioeconomic outcomes in the community. Further research is recommended for the specific impact of overhead transmission lines and substations on property values and tourism.